2021
DOI: 10.2807/1560-7917.es.2021.26.18.2100422
|View full text |Cite
|
Sign up to set email alerts
|

The silent epidemic of lymphogranuloma venereum inside the COVID-19 pandemic in Madrid, Spain, March 2020 to February 2021

Abstract: Despite social distancing measures implemented in Madrid to prevent the propagation of SARS-CoV-2, a significant increase (57.1%; 28.5 to 38.5 cases/month) in cases of lymphogranuloma venereum was detected during the COVID-19 pandemic. This unusual scenario might have accelerated a shift in Chlamydia trachomatis (CT) epidemiology towards a higher proportion of L genotypes compared with non-L genotypes in CT-positive samples. Our data underscore the importance of surveillance of sexually transmitted infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
2
0
2
Order By: Relevance
“…Further investigation will be needed to understand the impact of HIV prevention on transmission of bacterial STIs. However, the increasing proportion of LGV diagnoses among HIV-negative MSM during 2017–2019 is in line with reports from other countries in Europe ( 6 , 8 , 14 , 15 ).…”
Section: Discussionsupporting
confidence: 88%
“…Further investigation will be needed to understand the impact of HIV prevention on transmission of bacterial STIs. However, the increasing proportion of LGV diagnoses among HIV-negative MSM during 2017–2019 is in line with reports from other countries in Europe ( 6 , 8 , 14 , 15 ).…”
Section: Discussionsupporting
confidence: 88%
“…This is in accordance with recent European studies where an evolution towards this genovar has been observed [11][12][13]. Although LGV outbreaks were initially characterized as affecting predominantly HIV-positive MSM [14], recent European studies have reported a rising trend of LGV among HIV-negative MSM [15][16][17]; which is consistent with our finding of both HIV-positive and HIV-negative LGV case. The recommended therapy for LGV proctitis is oral doxycycline, 100 mg orally twice daily for three weeks [6].…”
Section: Discussionsupporting
confidence: 93%
“…Sin embargo, con la epidemia del VIH, hubo un aumento de los casos de LGV anorectal en comunidades de HSH de Europa y de E.U.A. 9,10 y posteriormente en España, Francia y Australia [2][3][4]11,12 . En Chile, el LGV no es una enfermedad de notificación obligatoria, por lo que su real incidencia podría estar subestimada.…”
Section: Caso Clínicounclassified
“…Como en el caso presentado, la gran mayoría de los HSH que han adquirido el LGV también tienen VIH y otras ITS 2,13 . Al igual que otras infecciones ulceradas, el…”
Section: Caso Clínicounclassified